Analytical solution of three-dimensional two-layer composite beam with interlayer slips. (15th October 2018) - Čas, B.; Planinc, I.; Schnabl, S.
Highlights: Analytical solution of a three-dimensional two-layer composite beam with interlayer slips is derived for the first time. Deformations in transverse XZ and lateral XY planes are mutually independent. The results can be used as a benchmark solution. Abstract: This paper focuses on development of a new mathematical model and its analytical solution for the analysis of the mechanical behavior of geometrically and materially linear three-dimensional (3D) two-layer composite beams with interlayer slips between the layers. Consequently, the analytical solution of the mechanical behavior of elastic 3D two-layer composite beams with interlayer slips is derived for the first time. In the illustrative example, the cantilever 3D two-layer timber-concrete composite beam with interlayer slips is analysed, and the analytical results for various kinematic and equilibrium quantities are given. Besides, it is demonstrated that in case of the shear-stiff 3D two-layer composite beams with interlayer slips, the deformations in transverse XZ and lateral XY planes are mutually independent. The results obtained can be used as a benchmark solution.